Patton’s Third Army at war - Muller, V.C. (Scientia Militaria - South African Journal of Military Studies, 2011)
In a series of accounts written by the men who ’were there’, the reader follows General George S. Patton and his Third Army through the North West European campaign of 1944 and 1945.